Using game concepts to improve programming learning: A multi‐level meta‐analysis - Costa, Joana M. (Computer applications in engineering education, 2023)
Gamification has been widely used in education due to its application to different contexts. The vast number of possibilities allows the creation of learning strategies that lead to students' success. Despite the high acceptance of gamification among several authors in educational contexts, there are many dispersed studies with high differences in their results. Although gamification impacts motivation, interest, and engagement, its effect on students' learning outcomes needs to be clarified. This study aims to investigate the effects of gamification on programming learning and the impact of the most used game concepts on knowledge acquisition. A multi‐level meta‐analysis was conducted on studies above K‐12 to understand the effects of gamification in programming learning. From 15 combined effect sizes, it was analyzed the effect of points, badges, levels, avatars, leaderboards, and the number of elements used. The results showed that gamification leads to a significant increase in the results (Cohen's d = 0.4) but essentially due to the use of levels (p < .05). Using badges, points, avatars, and leaderboards showed no significant effect on programming learning, suggesting that these elements may be more beneficial to motivating or engaging the students. Gamification can be efficient in programming learning, but it is recommended the use of levels.